Thermodynamic properties of quantum-corrected AdS black hole with phantom global monopoles - Bilel Hamil; Bekir Can Lütfüoğlu; Faizuddin Ahmed; Zeeshan Yousaf (Nuclear Physics B)
In this paper, we introduce a metric ansatz designed to describe spherically symmetric quantum-corrected black hole (BH) space-time within an AdS space background, incorporating both an ordinary and a phantom global monopole. Our study focus into the thermodynamic properties of this BH, where we compute key parameters such as the Hawking temperature and specific heat capacity. We then proceed to analyze the effective potential of the system, considering both null and time-like geodesics, and investigate the shadow radius of the BH. Additionally, we calculate the emission rate of particles from the BH, providing insights into the energy dynamics. The geodesic equations of motion are explored to visualize the trajectories of massive particles within the BH. Throughout our investigation, we thoroughly examine how the inclusion of both ordinary and phantom global monopoles, combined with the quantum-corrected parameter, influences various thermal properties, the effective potential of the system, the BH shadow radius, energy emission rate, and the trajectories of massive particles. Importantly, by generating figures that depict these phenomena, we emphasize the differences in results obtained with ordinary global monopoles and phantom ones, considering a range of quantum-corrected parameter values and small energy scale parameters, which allows us to discern the distinct effects of each type of monopole in the black hole's behavior.